Patient-related risk factors of prosthetic joint infections following total hip and knee arthroplasty at King Abdulaziz Medical City, a 10-year retrospective study - Wazzan S. Aljuhani; Abdullah M. Alanazi; Abdullah I. Saeed; Khalid H. Alhadlaq; Yazeed S. Alhoshan; Ziad A. Aljaafri (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background Total joint arthroplasty (TJA) can be associated with the development of periprosthetic joint infection (PJI). It is necessary to determine the modifiable and non-modifiable risk factors of PJI to provide optimum healthcare to TJA candidates. Methods This single-center retrospective review investigated 1198 patients who underwent TJA from 2012 to 2022. The data analysis comprised two stages. The first stage was a descriptive analysis, while the second stage was a bivariate analysis. The sociodemographic data, medical history, operative details, and presence of PJI postoperatively were evaluated. Results The study sample consisted of 1198 patients who underwent TJA. The mean patient age was 63 years. Among the patients, only 1.3% had PJI. No comorbidity was significantly related to PJI. General anesthesia was used in almost 21% of the patients and was significantly associated with a higher risk of infection (p = 0.049). An increased operative time was also significantly related to PJI (p = 0.012). Conversely, tranexamic acid (TXA) administration was a protective factor against PJI (p = 0.017). Conclusion Although PJI is not a common complication of TJA, multiple risk factors such as general anesthesia and prolonged operative time play a significant role in its development. In contrast, TXA administration is thought to reduce the risk of PJI effectively.